Ceramic membrane with super-hydrophobic pore channels and preparation method of ceramic membrane
By growing ZnO nanoparticles and forming ZnO nanoclusters on the surface of the ceramic membrane and its pores, and forming long silane link branches through hydrolysis reaction with n-octyltriethoxysilane, the problem of clogging the mass transfer channel due to water phase adhesion during membrane distillation, oil-water separation, membrane emulsification, etc., the high-efficiency superhydrophobic performance of the ceramic membrane is achieved.
Patent Information
- Application Number
- CN202510020647.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing ceramic membranes are prone to blocking the mass transfer channel due to water phase adhesion during membrane distillation, oil-water separation, membrane emulsification, etc., resulting in a decline in membrane performance.
ZnO nanoparticles were grown on the surface of the ceramic membrane and its pores through the sol dip coating-calcination method, and ZnO nanoclusters were formed by hydrothermal synthesis. Finally, long silane link branches were formed through hydrolysis reaction with n-octyltriethoxysilane, which enhanced the superhydrophobicity of the membrane.
The micro-nano composite multi-level structure on the surface of the ceramic membrane and its interior of the pores is realized, which significantly improves the superhydrophobicity of the membrane, thereby enhancing the repulsion to the water phase and extending the service life of the membrane.
Smart Images

Figure CN119746646A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic membrane with super-hydrophobic pores and a preparation method thereof, belonging to the technical field of ceramic membranes. Background Art
[0002] In recent years, membrane separation technology has emerged in the field of water treatment due to its advantages such as low energy consumption, small footprint, no secondary pollution and easy operation. Among them, ceramic membranes are expected to be used in harsh operating atmospheres due to their corrosion resistance, high temperature resistance, solvent resistance and long service life. However, since the surface of ceramic membranes usually has a high surface free energy, most oil phases and water phases are in a spreading state when they come into contact with the surface of ceramic membranes. When these ceramic membranes are used in membrane processes such as membrane distillation, oil-water separation, and membrane emulsification, it will be found that the water phase in the treated liquid is very easy to adhere to the membrane surface and penetrate into the membrane pores, thereby blocking the mass transfer channel and causing the membrane performance to decrease and lose. However, a large amount of research data shows that ceramic membranes modified with superhydrophobicity can effectively improve their repellency to the water phase to alleviate the occurrence of the above-mentioned membrane pollution phenomenon, thereby ensuring the efficient separation performance of the membrane. Therefore, the preparation method of ceramic membranes with superhydrophobic properties is of great significance for their application in separation fields such as membrane distillation, membrane emulsification, and oil-water separation.
[0003] At present, the common and effective method for constructing super-hydrophobic ceramic membranes is to construct a micro-nano composite multi-level structure on the membrane surface, and use organic silane or low surface free energy substances to reduce the membrane surface free energy. Chinese Patent No. CN112934012B discloses a method for super-hydrophobic modification of the surface of a tubular ceramic membrane based on polytetrafluoroethylene. First, ethyl cellulose-anhydrous ethanol sol is used as a colloidal coating aid, and an organic amine suspension of PTFE is added. After ultrasonic dispersion and stirring, a colloidal coating liquid is obtained; then, the colloidal coating liquid is coated on the ceramic membrane substrate by a pulling and impregnation method; finally, a tubular ceramic membrane with a super-hydrophobic surface is obtained after heat treatment in a tubular furnace. Chinese Patent No. CN111635258B discloses a TiO based ceramic membrane. 2 The super-hydrophobic modification method first obtains a titanium dioxide seed layer by dip-calcination and firmly fixes it on an alumina ceramic substrate; then, a hydrothermal reaction is used to generate titanium dioxide nanorods; finally, the ceramic membrane with titanium dioxide nanorods is immersed in a PDTS ethanol solution for hydrophobic treatment to obtain a super-hydrophobic ceramic membrane with a water contact angle of 152°. Although both of the above preparation methods can make the ceramic membrane super-hydrophobic, its super-hydrophobicity only stays on the surface of the membrane layer, and it is impossible to further make the inside of the membrane pores have super-hydrophobicity similar to the membrane surface.
[0004] Based on the above problems, how to provide a method for preparing a ceramic membrane with super-hydrophobic pores is an issue that technicians in this field urgently need to solve. Summary of the invention
[0005] The purpose of the present invention is to solve the problems and needs existing in the above-mentioned prior art, and to provide a ceramic membrane with super-hydrophobic pores and a preparation method thereof, so as to enhance the repulsion performance of the ceramic membrane pores to the water phase, and optimize the geometric configuration of the membrane to improve the comprehensive performance of the membrane.
[0006] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention includes a ceramic membrane with super-hydrophobic pores and a preparation method thereof, the specific contents of which are as follows:
[0007] A ceramic membrane with super-hydrophobic pores, comprising a membrane surface and pores thereof having a micro-nano composite multi-level structure and super-hydrophobicity; specifically, a sol-coating-calcination method is used to grow ZnO nanoparticles on the surface of a porous ceramic membrane and inside its pores; a hydrothermal synthesis method is then used to use the ZnO nanoparticles as a seed layer to grow ZnO nanoclusters on the surface of porous ceramic membrane bones; finally, a large number of hydroxyl groups on the surface of the ceramic membrane are hydrolyzed with n-octyltriethoxysilane to allow long silane chains to be grafted on the membrane surface, thereby obtaining a ceramic membrane with super-hydrophobic pores.
[0008] A method for preparing a ceramic membrane with super-hydrophobic pores comprises the following steps:
[0009] (1) mixing zinc acetate dihydrate, ethanolamine and ethylene glycol methyl ether in a certain ratio, and reacting the mixture at 60-70° C. for 60-180 min. After the reaction is completed, stirring the mixture at 20-30° C. for 3-6 h to obtain a zinc-based sol;
[0010] (2) immersing the porous ceramic membrane in the zinc-based sol obtained in step (1) for 5-30 seconds, taking it out and placing it in an oven at 80-100° C. for drying for 30-60 minutes, repeating the above operation 1-3 times, placing the dried membrane in a muffle furnace for high-temperature calcination, and taking it out after cooling to room temperature to obtain a ceramic membrane with grown ZnO nanoparticles;
[0011] (3) mixing zinc nitrate hexahydrate, hexamethylenetetramine and deionized water in a certain ratio, and stirring the mixture at 20-30° C. for 30-60 minutes to prepare a hydrothermal growth solution;
[0012] (4) placing the ceramic membrane calcined at high temperature in step (2) in a high-pressure reactor containing the hydrothermal growth solution obtained in step (3), and placing it in an oven for hydrothermal growth reaction; after cooling to room temperature, taking it out and rinsing it with deionized water for 10-20 seconds to obtain a ceramic membrane with grown ZnO nanoclusters;
[0013] (5) mixing n-octyltriethoxysilane and anhydrous ethanol in a certain ratio to prepare a silane grafting solution;
[0014] (6) Immerse the ceramic membrane after the hydrothermal reaction in step (4) in the silane grafting solution obtained in step (5) for reaction for 10-16 hours at a reaction temperature of 40-50°C. After the reaction is completed, take out the ceramic membrane and rinse it, then transfer it to an oven at 80-120°C for drying for 2-3 hours, and take it out after cooling to obtain a ceramic membrane with super-hydrophobic pores.
[0015] Furthermore, in the above step (1), the ratio of zinc acetate dihydrate, ethanolamine and ethylene glycol methyl ether is 6-10 g: 3-5 mL: 30-50 mL.
[0016] Furthermore, in the above step (2), the temperature in the furnace of the muffle furnace is 400-500° C., the heating rate is 2-5° C. / min, the calcination atmosphere is air, and the calcination time is 200-300 min.
[0017] Furthermore, in the above step (3), the mass ratio of zinc nitrate hexahydrate, hexamethylenetetramine and deionized water is 1-1.5:2-2.5:80-100.
[0018] Furthermore, in the above step (4), the hydrothermal growth temperature is 80-120° C., and the hydrothermal growth time is 4-12 hours.
[0019] Furthermore, in the above step (5), the volume fraction of n-octyltriethoxysilane and anhydrous ethanol is 5-10 vol%.
[0020] Furthermore, in the above step (6), after the membrane is soaked in the silane grafting solution for reaction, it is rinsed with anhydrous ethanol, anhydrous ethanol-deionized water solution, and deionized water in sequence for 10-20 seconds.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The ceramic membrane with super-hydrophobic pores provided by the present invention has a micro-nano composite multi-level structure on the membrane surface and inside the pores, and the micro-nano composite multi-level structure has low surface free energy and can greatly improve the hydrophobicity of the ceramic membrane surface and inside the pores.
[0023] The invention provides a method for preparing a ceramic membrane with super-hydrophobic pores. The obtained zinc-based sol can better promote the growth of ZnO nanoparticles on the surface of the ceramic membrane and inside its pores in a sol dipping-calcination method; the obtained silane grafting solution can better promote the growth of ZnO nanoclusters in a hydrothermal growth reaction; under the promotion of both, a more stable micro-nano composite multi-level structure can be formed on the surface of the ceramic membrane and inside its pores. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the embodiments or the description of the prior art are briefly introduced below.
[0025] Figure 1 The present invention is a flow chart of the preparation process of a ceramic membrane with super-hydrophobic pores according to an embodiment of the present invention;
[0026] Figure 2 The SEM images of the surface and cross-section (upper right corner) of different ceramic membranes in the embodiments of the present invention, wherein (a) is the original silicon carbide ceramic membrane (SiC-0), (b) is the silicon carbide ceramic membrane with super-hydrophobic channels grown hydrothermally for 4 hours (SiC-1), and (c) is the silicon carbide ceramic membrane with super-hydrophobic channels grown hydrothermally for 8 hours (SiC-2);
[0027] Figure 3 The pore size distribution diagram of the SiC-0 film, SiC-1 film, and SiC-2 film involved in the embodiments of the present invention;
[0028] Figure 4 This is a static water contact angle test diagram of the original ceramic membrane used in the embodiment of the present invention;
[0029] Figure 5 The static water contact angle test diagram of two ceramic membranes with super-hydrophobic pores prepared in the embodiments of the present invention. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a ceramic membrane having super-hydrophobic pores, such as Figure 1 As shown, the present invention is further described in detail below in conjunction with specific embodiments, but the present invention is not limited thereto.
[0031] Example 1
[0032] (1) Preparation of sol: 10 g zinc acetate dihydrate, 5 mL ethanolamine, and 50 mL ethylene glycol methyl ether were weighed and mixed, and the mixture was reacted at 70° C. and a stirring speed of 500 r / min for 120 min until the zinc-based colloid turned light yellow. The mixture was then moved to room temperature and stirred for 6 h.
[0033] (2) Growth of nanoparticles: The silicon carbide ceramic membrane is fully immersed in the zinc-based sol for 15 seconds. After being evenly immersed, it is taken out from the sol at a uniform and slow speed, and then placed in a 100°C oven to dry for 60 minutes. After repeating the above operation twice, the dried membrane is placed in a muffle furnace for calcination at a heating rate of 2°C / min, a calcination temperature of 400°C, and a calcination time of 200 minutes. After cooling to room temperature, it is taken out to obtain a silicon carbide ceramic membrane with grown ZnO nanoparticles.
[0034] (3) Growth of nanoclusters: Weigh 1g of hexamethylenetetramine, 2g of zinc nitrate hexahydrate, and 80mL of deionized water, respectively, and stir at room temperature for 60min at a stirring speed of 500r / min to obtain a hydrothermal growth solution. Transfer the silicon carbide ceramic membrane on which ZnO nanoparticles are grown and the hydrothermal growth solution into a 150mL polytetrafluoroethylene-lined autoclave at the same time, and keep the temperature at 100°C for 6h. When the temperature drops to room temperature, take out the sample and clean the surface impurities with deionized water to obtain a silicon carbide ceramic membrane on which ZnO nanoclusters are grown.
[0035] (4) Silane chemical grafting treatment: The silicon carbide ceramic membrane with grown ZnO nanoclusters was immersed in a 10 vol% n-octyltriethoxysilane-anhydrous ethanol solution for 12 h. After the reaction was completed, the membrane was taken out and rinsed with anhydrous ethanol, anhydrous ethanol-deionized water solution, and deionized water in sequence, and then placed in an oven at 80°C for 3 h to obtain a SiC-1 membrane.
[0036] The average pore size of the silicon carbide ceramic membrane with super-hydrophobic channels prepared in this example is 255.9 nm, the porosity is 35.09%, the water contact angle is 157.9°, and the pure n-hexane flux is 4157.52 L·m -2 ·h -1 bar -1 .
[0037] Example 2
[0038] (1) Preparation of sol: 10 g zinc acetate dihydrate, 5 mL ethanolamine, and 50 mL ethylene glycol methyl ether were weighed and mixed, and the mixture was reacted at 70° C. and a stirring speed of 500 r / min for 120 min until the zinc-based colloid turned light yellow. The mixture was then moved to room temperature and stirred for 6 h.
[0039] (2) Growth of nanoparticles: The silicon carbide ceramic membrane is fully immersed in the zinc-based sol for 15 seconds. After being evenly immersed, it is taken out from the sol at a uniform and slow speed, and then placed in a 100°C oven to dry for 60 minutes. After repeating the above operation twice, the dried membrane is placed in a muffle furnace for calcination at a heating rate of 2°C / min, a calcination temperature of 400°C, and a calcination time of 200 minutes. After cooling to room temperature, it is taken out to obtain a silicon carbide ceramic membrane with grown ZnO nanoparticles.
[0040] (3) Growth of nanoclusters: Weigh 1g of hexamethylenetetramine, 2g of zinc nitrate hexahydrate, and 80mL of deionized water, mix them, stir them at room temperature for 60min, and the stirring speed is 500r / min to obtain a hydrothermal growth solution. Transfer the silicon carbide ceramic membrane with grown ZnO nanoparticles and the hydrothermal growth solution into a 150mL polytetrafluoroethylene-lined autoclave at the same time, and keep them at 100°C for 12h. When the temperature drops to room temperature, take out the sample and clean the surface impurities with deionized water to obtain a silicon carbide ceramic membrane with grown ZnO nanoclusters.
[0041] (4) Silane chemical grafting treatment: The silicon carbide ceramic membrane with grown ZnO nanoclusters was immersed in a 10 vol% n-octyltriethoxysilane-anhydrous ethanol solution for 12 h. After the reaction was completed, the membrane was taken out and rinsed with anhydrous ethanol, anhydrous ethanol-deionized water solution, and deionized water in sequence, and then placed in an oven at 80°C for 3 h to obtain a SiC-2 membrane.
[0042] The average pore size of the silicon carbide ceramic membrane with super-hydrophobic channels prepared in this example is 194.6 nm, the porosity is 34.44%, the water contact angle is 163.9°, and the pure n-hexane flux is 4625.18 L·m -2 ·h -1 bar -1 .
[0043] See also Figure 2 From the scanning electron microscope images shown, it can be seen that the original silicon carbide ceramic membrane (SiC-0) used is formed by the accumulation of SiC bone particles, and the surface and cross-section show a regular porous morphology. After the superhydrophobic modification treatment in the above steps, uniform and regular ZnO nanoclusters grow on the surface of SiC-1 and SiC-2 membranes and inside their pores.
[0044] See also Figure 3 The pore size distribution diagram of different silicon carbide ceramic membranes shown in the figure shows that the average pore size of the original ceramic membrane is about 350nm. After the superhydrophobic modification treatment in the above steps, the membrane pores become smaller due to the growth of ZnO nanoclusters, and as the hydrothermal growth time increases, the average pore size of the ceramic membrane becomes smaller. The average pore size of the SiC-1 membrane is 255.9nm, and the average pore size of the SiC-2 membrane is 194.6nm.
[0045] The original silicon carbide ceramic membrane sample was tested for water contact angle. The test results are as follows: Figure 4 As shown in Figure 2, the static water contact angle of the SiC-0 membrane surface is only 8.3°. After the super-hydrophobic treatment in the above steps, the water contact angle of the silicon carbide ceramic membrane sample with super-hydrophobic pores is tested. The test results are shown in Figure 2. Figure 5As shown in the figure, the water contact angle on the surface of SiC-1 membrane is 157.9°, and the water contact angle on the surface of SiC-2 membrane is 163.9°. Although the hydrophobicity inside the membrane pores cannot be evaluated using this characterization method, by observing the scanning electron microscope image of the silicon carbide ceramic membrane with ZnO nanoclusters growing on it ( Figure 2 bc) It can be determined that the interior of the membrane pores has a micro-nano composite multi-level structure similar to that of the membrane surface. The ceramic membrane with a micro-nano composite multi-level structure in the pores can graft the long alkyl chain of the organic silane on the ceramic membrane after the hydrolysis reaction of the organic silane, so that the membrane surface and the interior of the pores have similar chemical components. Therefore, the wettability of the ceramic membrane surface can indirectly reflect the wettability of the interior of the ceramic membrane pores.
Claims
1. A ceramic membrane with super-hydrophobic pores, characterized in that: The ceramic membrane with super-hydrophobic pores comprises a membrane surface and its pores with a micro-nano composite multi-level structure and super-hydrophobicity; specifically, a sol-gel dipping-calcination method is used to grow ZnO nanoparticles on the surface of the porous ceramic membrane and its pores; a hydrothermal synthesis method is then used to grow ZnO nanoclusters on the surface of the porous ceramic membrane bone particles using the ZnO nanoparticles as a seed layer; finally, a large number of hydroxyl groups on the surface of the ceramic membrane are hydrolyzed with n-octyltriethoxysilane to allow long silane chains to be grafted on the membrane surface, thereby obtaining a ceramic membrane with super-hydrophobic pores.
2. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 1, characterized in that: The method comprises the following steps: (1) mixing zinc acetate dihydrate, ethanolamine and ethylene glycol methyl ether in a certain ratio, and reacting the mixture at 60-70° C. for 60-180 min. After the reaction is completed, stirring the mixture at 20-30° C. for 3-6 h to obtain a zinc-based sol; (2) immersing the porous ceramic membrane in the zinc-based sol obtained in step (1) for 5-30 seconds, taking it out and placing it in an oven at 80-100° C. for drying for 30-60 minutes, repeating the above operation 1-3 times, placing the dried membrane in a muffle furnace for high-temperature calcination, and taking it out after cooling to room temperature to obtain a ceramic membrane with grown ZnO nanoparticles; (3) mixing zinc nitrate hexahydrate, hexamethylenetetramine and deionized water in a certain ratio, and stirring the mixture at 20-30° C. for 30-60 minutes to prepare a hydrothermal growth solution; (4) placing the ceramic membrane calcined at high temperature in step (2) in a high-pressure reactor containing the hydrothermal growth solution obtained in step (3), and placing it in an oven for hydrothermal growth reaction; after cooling to room temperature, taking it out and rinsing it with deionized water for 10-20 seconds to obtain a ceramic membrane with grown ZnO nanoclusters; (5) mixing n-octyltriethoxysilane and anhydrous ethanol in a certain ratio to prepare a silane grafting solution; (6) Immerse the ceramic membrane after the hydrothermal reaction in step (4) in the silane grafting solution obtained in step (5) for reaction for 10-16 hours at a reaction temperature of 40-50°C. After the reaction is completed, take out the ceramic membrane and rinse it, then transfer it to an oven at 80-120°C for drying for 2-3 hours, and take it out after cooling to obtain a ceramic membrane with super-hydrophobic pores.
3. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: In the step (1), the ratio of zinc acetate dihydrate, ethanolamine and ethylene glycol methyl ether is 6-10 g: 3-5 mL: 30-50 mL.
4. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: In the step (2), the temperature in the furnace of the muffle furnace is 400-500° C., the heating rate is 2-5° C. / min, the calcination atmosphere is air, and the calcination time is 200-300 min.
5. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: In the step (3), the mass ratio of zinc nitrate hexahydrate, hexamethylenetetramine and deionized water is 1-1.5:2-2.5:80-100.
6. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: In the step (4), the hydrothermal growth temperature is 80-120° C., and the hydrothermal growth time is 4-12 hours.
7. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: The volume fraction of n-octyltriethoxysilane and anhydrous ethanol in step (5) is 5-10 vol%.
8. The method for preparing a ceramic membrane having super-hydrophobic pores according to claim 2, characterized in that: In the step (6), after the membrane is soaked in the silane grafting solution for reaction, it is rinsed with anhydrous ethanol, anhydrous ethanol-deionized water solution, and deionized water in sequence for 10-20 seconds.
Citation Information
Patent Citations
A method for superhydrophobic modification of TiO2 based on ceramic membranes
CN111635258B
A method for superhydrophobic modification of tubular ceramic membrane surfaces based on polytetrafluoroethylene
CN112934012B
Method for preparing hydrophobic ceramic membrane
CN108126532A
Super-hydrophobic silicon carbide ceramic membrane and preparation method thereof
CN114685188A
Cited By
Electric porcelain insulator with wear-resistant hydrophobic structure and preparation method thereof
CN120289210A
Water treatment filtering material and preparation method thereof
CN120618275A
A water treatment filter material and a method of making the same
CN120618275B
Hydrophobic ceramic membrane for CMP wastewater treatment and preparation method thereof
CN121648750A